2019
DOI: 10.1038/s41598-019-52216-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurons in the pigeon nidopallium caudolaterale, but not the corticoidea dorsolateralis, display value and effort discounting activity

Abstract: We recorded from single neurons in two areas of the pigeon brain while birds were required to peck a stimulus indicating either a high effort task or a low effort task would follow. Upon completion of the task the birds received the same reward. We found that activity in the nidopallium caudolaterale, an area equivalent to the mammalian prefrontal cortex, was modulated by the value of the reward that would be received based on how much effort was required to obtain it. Value coding was most prominent during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Further study has indicated that the increased gamma band (40–60 Hz) energy of local field potential (LFP) in NCL is significantly correlated to the goal-directed behavior during the decision-making process [ 63 ], and the functional connectivity of the functional network based on the multi-channel spike and LFP activities in NCL can be used for goal-directed behavioral outcomes decoding effectively [ 64 ], confirming the role of NCL in the navigational behavior of pigeon on different scales. In addition, for the reward encoding in goal-directed behavior, studies have shown that the activities of NCL were modulated by the value of the reward that would be received based on the reward amount and the delay to reward [ 65 , 66 ], which confirms that NCL has the function of reward encoding to achieve a specific purpose. On the other hand, the NCL neuronal responses during serial-order behavior in pigeons also confirmed that NCL encoded the planning and working memory content containing ordinal knowledge [ 67 , 68 ], which could imply the important role of NCL in the goal-directed navigation, a typical serial-order behavior.…”
Section: The Role Of Ncl In Goal-directed Route Information Encodimentioning
confidence: 98%
“…Further study has indicated that the increased gamma band (40–60 Hz) energy of local field potential (LFP) in NCL is significantly correlated to the goal-directed behavior during the decision-making process [ 63 ], and the functional connectivity of the functional network based on the multi-channel spike and LFP activities in NCL can be used for goal-directed behavioral outcomes decoding effectively [ 64 ], confirming the role of NCL in the navigational behavior of pigeon on different scales. In addition, for the reward encoding in goal-directed behavior, studies have shown that the activities of NCL were modulated by the value of the reward that would be received based on the reward amount and the delay to reward [ 65 , 66 ], which confirms that NCL has the function of reward encoding to achieve a specific purpose. On the other hand, the NCL neuronal responses during serial-order behavior in pigeons also confirmed that NCL encoded the planning and working memory content containing ordinal knowledge [ 67 , 68 ], which could imply the important role of NCL in the goal-directed navigation, a typical serial-order behavior.…”
Section: The Role Of Ncl In Goal-directed Route Information Encodimentioning
confidence: 98%